An Empirical Study: Suzuki All-New Ertiga Purchase Decision Based on Product Quality and Promotion at PT. Trans Sumatra Mainstay Sisingamangaraja Branch-Medan - Saila Mutiya Nasution; Abd. Rasyid Syamsuri; Hardi Mulyono; Arief Hadian (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study's goal was to analyze the effect of product quality and promotion on purchasing decisions for the Suzuki All New Ertiga at PT. Trans Sumatra Mainstay Sisingamangaraja Branch. The research was carried out between March 2021 and June 2022 and employs a quantitative methodology. The data collection techniques employed are observations, documentation studies, and surveys on a Likert scale. Using Isaac and Michael's calculation formula, a sample of 162 clients from PT. The Sisingamangaraja Mainstay Branch of Trans Sumatra represents a fraction of the research population of up to 400 persons. The SPSS program's multiple linear regression analysis technique. According to the study's findings, a positive and significant influence on purchases is provided by product quality. Promotions have positive and significant influence on purchasing decisions. At PT. Mainstay of Trans Sumatra Sisingamangaraja Branch, promotion and overall product quality have a positive and significant impact on purchasing decisions. The quality of the product and the promotion can explain 91.9 percent of consumer purchasing decisions, according to the study's coefficient of determination (R2), which is 0.919.